miR-15a-5p regulates myocardial fibrosis in atrial fibrillation by targeting Smad7 - Dan He; Zhong-bao Ruan; Gui-xian Song; Ge-cai Chen; Fei Wang; Mei-xiang Wang; Mao-kun Yuan; Li Zhu (PeerJ, 2021)
Background At present, there is no effective treatment for myocardial fibrosis in atrial fibrillation (AF). It is reported that miR-15a-5p is abnormally expressed in AF patients but its specific role remains unclear. This study aims to investigate the effect of miR-15a-5p in myocardial fibrosis. Methods Left atrial appendage (LAA) tissues were collected from AF and non-AF patients. In lipopolysaccharide (LPS) stimulated H9C2 cells, miR-15a-5p mimic, inhibitor, pcDNA3.1-Smad7 and small interfering RNA-Smad7 (siRNA-Smad7) were respectively transfected to up-regulate or down-regulate the intracellular expression levels of miR-15a-5p and Smad7. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blot (WB) were used to determine the expression levels of miR-15a-5p, Smad7, transforming growth factor β1 (TGF-β1) and collagen I. Cell counting kit-8 (CCK-8) and ethylene deoxyuridine (EdU) were used to determine cell viability and proliferation capacity, respectively. Dual-luciferase was used to detect whether miR-15a-5p interacted with Smad7, hydroxyproline (HYP) and Hematoxylin-Eosin (HE) staining were used to detect tissue fibrosis. Results The expression levels of miR-15a-5p, TGF-β1 and collagen I were up-regulated, while Smad7 was down-regulated in AF tissues and LPS-stimulated cells. MiR-15a-5p mimic can inhibit the expression of Smad7, and the dual-luciferase experiment confirmed their interaction. MiR-15a-5p inhibitor or pcDNA3.1-Smad7 can inhibit LPS-induced fibrosis and cell proliferation, while siRNA-Smad7 can reverse the changes caused by miR-15a-5p inhibitor. Conclusion We combined clinical studies with LPS-stimulated H9C2 cell model to validate the role of miR-15a-5p in the regulation of Smad7 and fibrosis. Taken together, the miR-15a-5p/Smad7 pathway might be a potential target for AF therapy.